Preparation method and application of antibacterial tea-plastic composite material

By fixing antibacterial metal ions and polyphenols in tea residue, antibacterial tea-plastic composite materials are prepared, which solves the problem of short-term antibacterial properties of WPC materials, and achieves efficient and stable antibacterial effects and good mechanical properties. It is suitable for Public places for use.

CN119192806APending Publication Date: 2024-12-27武夷学院
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411491880.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Existing WPC composite materials are susceptible to mold and decaying fungi during use, resulting in short-term and unstable antibacterial properties, making it difficult to meet advanced functional needs, especially in public places for safety hazards.

Method used

By condensing the polyphenols in the tea residue with formaldehyde, antibacterial metal ions such as silver, zinc, and copper are fixed, forming inorganic metal ions/plant polyphenol composite antibacterial tea powder, and combining them with resin to prepare antibacterial tea plastics Composite materials ensure stable distribution of antibacterial agents within the material and avoid loss and agglomeration.

Benefits of technology

It has achieved an antibacterial rate of more than 99% against E. coli and Staphylococcus aureus, has long-term antibacterial properties and good mechanical properties, is low in cost and is suitable for the manufacture of imitation wood composite materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192806A_ABST
    Figure CN119192806A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method and application of an antibacterial tea-plastic composite material, plant polyphenol / inorganic metal-loaded composite antibacterial tea powder is prepared through continuous two-step in-situ modification, and meanwhile, a polyphenol / metal-loaded composite antibacterial agent is uniformly dispersed into macromolecular resin through a mixing process; wherein the tea residues are rich in source, cheap and easy to obtain, so that the antibacterial composite material is low in cost; the polyphenol antibacterial component is polymerized in situ and cured inside, so that instability and easy migration loss of a phenol antibacterial agent are avoided; the inorganic antibacterial agent is loaded inside by static electricity or complexation and the like in an ion form, the dispersity is good, the mechanical property of the antibacterial composite material is not affected, the problems that the inorganic antibacterial agent is difficult to disperse, not firm in combination and the like are solved, and the antibacterial composite material is endowed with stable and long-acting performance due to introduction of the inorganic antibacterial agent. The prepared antibacterial material organically integrates the advantages of the tea grounds, the polyphenol and the inorganic antibacterial agent, and has the characteristics of low cost, good mechanical property, good stability, long antibacterial time and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of composite material preparation, and specifically relates to a preparation method and application of an antibacterial tea-plastic composite material. Background Art

[0002] Wood-like composite materials, also known as plant fiber reinforced resin composite materials (wood plastics composites, WPC), are a new type of environmentally friendly composite materials prepared by mixing, molding, extrusion or injection molding with plant fibers or granules as the reinforcement phase and thermoplastic resins such as PP, PE and PVC as the matrix. They can be used in the construction market, home decoration, packaging and transportation, and automotive interior decoration. The production and application of WPC has important practical and strategic significance for the development and utilization of biological resources and the reduction of "white pollution". At present, we are still constantly seeking and expanding the types and sources of plant fillers in WPC materials.

[0003] Tea is one of the most popular beverages in the world besides water. Currently, the global annual tea consumption is nearly 6 million tons. China is the world's largest tea planting, production and consumption country. In the process of planting, production, processing and consumption, tea will produce a large amount of tea industry residues in various forms, such as tea tree pruning branches and leaves, tea stems and tea powder, tea scraps, low-grade tea, unsalable tea, etc. China alone can produce more than 5 million tons of tea residues each year. Tea residues are a cheap and readily available biomass fiber material, which is similar to wood fiber materials and can be used in the manufacture of WPC composite materials. Tea residues are rich in polyphenol components, which can also give composite materials certain antibacterial and anti-ultraviolet functions.

[0004] With the application and development of WPC composite materials, it is found that many mildew and decay fungi will harm, infect and even degrade WPC composite materials, significantly reduce the quality of WPC composite materials, and greatly affect their performance and service life. In addition, with the improvement of people's living standards, people's requirements for the functionalization of WPC composite materials are getting higher and higher, requiring WPC composite materials to have antibacterial and anti-mildew effects when used in public places such as hospitals, toilets, and parks.

[0005] Antimicrobial agents are key components for making antimicrobial WPC materials. Antimicrobial agents can be divided into three types: inorganic antimicrobial agents, organic antimicrobial agents, and polymer antimicrobial agents. At present, the antimicrobial modification of WPC composite materials is mainly achieved by adding inorganic antimicrobial agents, organic antimicrobial agents, and their complexes in the material formula by blending, or by grafting or coating antimicrobial components on the surface of WPC materials. Although the process operation is relatively simple, the organic antimicrobial components in WPC are easy to migrate and lose, and inorganic antimicrobial agents often have poor compatibility with WPC, weak bonding, and easy agglomeration. The antimicrobial components on the surface of WPC are lost due to rain, ultraviolet rays, and external friction. The presence of these unfavorable factors will cause WPC composite materials to lose their antimicrobial properties in a relatively short period of time. Therefore, how to obtain efficient and long-lasting antimicrobial properties is an urgent problem that the WPC material industry needs to solve. Summary of the invention

[0006] In view of the problems existing in the prior art, the present invention provides a method for preparing an antibacterial tea-plastic composite material and its application. The composite material has a simple preparation process, abundant raw materials, good mechanical properties and antibacterial properties, and its antibacterial rate against Escherichia coli and Staphylococcus aureus can reach more than 99%.

[0007] In order to achieve the above object, the present invention adopts the following technical solution: An antibacterial tea-plastic composite material, calculated by taking the sum of weight percentages as 100%, the contents of various components are: 10-50% antibacterial modified tea powder, 5-20% bulking agent, 30-85% resin, and 0.5-2% lubricant.

[0008] The method for preparing the antibacterial tea-plastic composite material comprises the following steps: (1) Preparation of tea powder: Wash the tea residues, air dry, grind them, and then sieve them to obtain tea powder; (2) Preparation of tea powder modified by in-situ polymerization of polyphenols: Add tea powder to hydrochloric acid solution, then add formaldehyde to react for a certain period of time, filter, and wash with water until the filtrate is neutral; (3) Preparation of antibacterial modified tea powder: adding the above-mentioned polyphenol in-situ solidified tea powder to an aqueous solution of inorganic antibacterial metal ions to react to obtain a composite antibacterial tea powder loaded with inorganic metal ions / plant polyphenols, namely, the antibacterial modified tea powder; (4) Preparation of antibacterial tea-plastic composite materials: Antibacterial modified tea powder, bulking agent, resin and lubricant are put into a color mixer and mixed evenly. The mixture is then transferred to a mixer. After mixing evenly, the material is discharged and crushed into pellets using a plastic crusher. The antibacterial tea-plastic composite material is obtained by injection molding.

[0009] Furthermore, the tea residue in step (1) is sourced from any one or any combination of tea tree branches, tea stems, tea powder, tea leaves, and tea processing waste, and has a particle size of 75-180 μm.

[0010] Furthermore, in step (2), the material-liquid ratio of tea powder to hydrochloric acid solution is 1:10-1:50, the concentration of hydrochloric acid solution is 0.2-0.6 mol / L, the mass fraction of formaldehyde added is 0.1-0.9% of the mass of tea powder, the reaction temperature is 50-80°C, and the reaction time is 1-3 h.

[0011] Furthermore, the inorganic antibacterial ions in step (3) are one or more of silver ions, zinc ions and copper ions, the sources of the inorganic metal ions are the corresponding silver nitrate, zinc nitrate and copper nitrate, respectively, the concentration of the inorganic antibacterial ions is 50-1000 mg / L, the solid-liquid ratio of the polyphenol in-situ solidified tea powder and the aqueous solution of the inorganic antibacterial metal ions is 1:20-1:200, the reaction temperature is room temperature, and the reaction time is 0.5-4 h.

[0012] Furthermore, in the step (4), the resin is one or more of polylactic acid (PLA), polypropylene (PP), and high-density polyethylene (HDPE); the compatibilizer is glycidyl methacrylate grafted resin; and the lubricant is at least one of stearic acid, polyethylene wax, zinc stearate, calcium stearate, and bis-stearic acid amide.

[0013] Furthermore, in the step (4), the mixing temperature is 140-180°C, the mixing time is 5-8 min, and the mixing speed is 40-60 r / min.

[0014] Furthermore, the four-stage temperatures of the injection molding in step (4) are 150-190°C, 150-190°C, 150-190°C, and 80-120°C, the injection pressure is 50-100 MPa, the injection time is 3-5 s, and the cooling time is 15-45 s.

[0015] The basic principle of the present invention is: Taking advantage of the fact that tea dregs are rich in polyphenol active components, based on the phenolic condensation mechanism, polyphenols and formaldehyde undergo phenolic condensation and are fixed in situ inside the tea dregs, so that the natural polyphenol antibacterial agent is retained inside the tea dregs as much as possible to reduce loss. Then, through the adsorption and complexation of polymerized polyphenols and metal ions, the inorganic antibacterial agent Ag is + 、Zn 2+ Cu 2+ A composite antibacterial tea powder loaded with plant polyphenols / inorganic metals was prepared by in-situ loading on polyphenol-cured tea residues through two consecutive in-situ modifications. It was then used as a functional filler and compounded with a polymer resin to prepare a new type of antibacterial wood-like composite material through a mixing process.

[0016] Compared with the prior art, the present invention has the following beneficial effects: (1) The antibacterial composite material prepared by the present invention organically integrates the advantages of tea biomass, polyphenols and inorganic antibacterial agents, has a synergistic effect, and presents the advantages of low cost, good mechanical properties, good stability, and long antibacterial effect. The tea residue in the composite material is abundant in source, cheap and easy to obtain, which gives the antibacterial composite material the advantage of low cost; polyphenol antibacterial agents have a fast antibacterial effect, but are easily soluble in rainwater or solvents. The polyphenol components in the tea residue are polymerized in situ and solidified inside the tea residue, avoiding the instability of phenol antibacterial agents and the defects of easy migration and loss during use. The introduction of the polyphenol components gives the composite material a rapid antibacterial effect; the inorganic antibacterial agent is loaded inside by electrostatic adsorption or complexation in the form of ions, and is introduced into the material at the molecular size level, avoiding the defect that conventional inorganic compound antibacterial agents are easy to agglomerate when added in solid powder, and has better dispersibility, does not affect the mechanical properties of the composite material, and solves the problems of difficult dispersion of inorganic antibacterial agents and weak binding with carriers. The introduction of the polyphenol components gives the antibacterial composite material stability and long-term effect. It is more suitable for the manufacture of antibacterial wood-like composite materials than simply adding organic polyphenol antibacterial agents or inorganic antibacterial agents.

[0017] (2) The antibacterial composite material prepared by the present invention has a significant and long-lasting antibacterial effect despite the low content of the introduced antibacterial components. The introduced metal ion content is as low as less than 1% of the mass of the composite material, and still meets the Class I antibacterial effect. The antibacterial rates of the composite material against Escherichia coli and Staphylococcus aureus are both above 99%. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is an electron microscope image of the interface morphology of the antibacterial tea-plastic composite material prepared in Example 2.

[0019] Figure 2 This is a graph showing the inhibition of Escherichia coli growth by the antibacterial tea-plastic composite material prepared in Example 2.

[0020] Figure 3 This is a graph showing the inhibition of Staphylococcus aureus growth by the antibacterial tea-plastic composite material prepared in Example 2.

[0021] Figure 4 This is a graph showing the inhibition of Escherichia coli growth by the antibacterial tea-plastic composite material prepared in Comparative Example 4.

[0022] Figure 5 This is a graph showing the inhibition of Staphylococcus aureus growth by the antibacterial tea-plastic composite material prepared in Comparative Example 4. DETAILED DESCRIPTION

[0023] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.

[0024] The tea residues involved in the following embodiments are derived from any one or any combination of tea tree branches, tea stems, tea powder, tea leaves, and tea processing waste, and have a particle size of 75-180 μm.

[0025] The silver ion solution in the following examples is prepared by first dissolving 7.8740 g of silver nitrate in deionized water, transferring the solution to a 1000 mL brown volumetric flask to a constant volume to obtain a 5000 mg / L silver ion mother solution (concentration based on metal ions), which is then diluted.

[0026] The copper ion solution in the following examples is prepared by first dissolving 19.0100 g of copper nitrate trihydrate in deionized water, transferring the solution to a 1000 mL volumetric flask to a constant volume to obtain a 5000 mg / L copper ion mother solution (concentration based on metal ions), which is then diluted.

[0027] The zinc ion solution in the following examples is obtained by first dissolving 22.7408 g of zinc nitrate hexahydrate in deionized water, transferring the solution to a 1000 mL volumetric flask to a constant volume to obtain a 5000 mg / L zinc ion mother solution (concentration based on metal ions), and then diluting the solution.

[0028] Example 1 (1) Preparation of tea powder: The tea residue was rinsed with clean water, dried, and then air-dried at 80 °C for 12 h. It was then crushed with a plant grinder and the tea powder with a particle size of 75-180 μm was collected using a standard sample sieve.

[0029] (2) Preparation of tea powder modified by in-situ polymerization of polyphenols: The solid-liquid ratio (tea powder: hydrochloric acid) was fixed at 1:20. 5.0 g of tea powder was added to 100 mL of 0.5 mol / L hydrochloric acid solution. Then, formaldehyde (0.1% by mass of the tea powder) was added. The mixture was reacted at 60 °C for 2 h. The mixture was then filtered and washed with water until the pH of the filtrate was neutral. The filtrate was then dried at 80 °C for 12 h for later use.

[0030] (3) Preparation of antibacterial modified tea powder: The solid-liquid ratio (polyphenol in situ polymerization modified tea powder: silver ion solution) was fixed at 1:100, and the above-mentioned polyphenol in situ solidified tea powder was added to a silver ion solution with a concentration of 1000 mg / L. After adsorption in a water bath at room temperature for 0.5 h, the mixture was filtered, and the residue was collected and dried at 80 °C for 12 h for later use. The collected residue was the silver ion-loaded modified tea powder, i.e., the antibacterial modified tea powder.

[0031] (4) Preparation of composite materials: 10% antibacterial modified tea powder, 84% polylactic acid (PLA), 5% glycidyl methacrylate grafted polylactic acid, and 1% stearic acid were added into a color mixer according to their mass percentage and mixed evenly; the mixture was transferred into a mixer and mixed at 180 °C for 7 min at a mixing speed of 50 r / min, and then crushed into pellets using a plastic crusher. The mixed pellets were injection molded at four injection molding temperatures of 190 °C, 190 °C, 190 °C, and 90 °C, an injection pressure of 50 MPa, an injection time of 4 s, and a cooling time of 30 s.

[0032] Prepared wt %=10% silver-loaded polyphenol-cured tea residue / polylactic acid composite material, wherein the silver content of the composite material is 0.248%. The tensile properties of the antibacterial tea-plastic composite material were tested using an AGS-X universal material testing machine (Shimadzu Instrument Co., Ltd., Japan) according to GB / T1040.2-2022, with a loading speed of 5 mm / min and a sample size of 150.0 mm×10.0 mm×4.0 mm. The flexural strength of the composite material was tested using a universal material testing machine according to GB / T9341-2008, with a span of 60 mm, a test speed of 2 mm / min, and a sample size of 100.0 mm×10.0 mm×4.0 mm. The simply supported beam notched impact strength of the composite material was tested using a ZBC7251-B liquid crystal plastic pendulum impact testing machine (Mester Industrial Systems Co., Ltd.) according to GB / T1043.1-2008. The antibacterial properties of the composite material were tested according to the industry standard QBT 2591-2003 "Test Methods and Antibacterial Effects of Antibacterial Plastics". The tensile strength of the antibacterial composite material was 65.4 MPa and the flexural strength was 117.9 MPa, notched impact strength is 25.9 J / m, the antibacterial rate against Escherichia coli is 99.3%, and the antibacterial rate against Staphylococcus aureus is 100%. The test method is the same below.

[0033] Example 2 (1) Preparation of tea powder: The tea residue was rinsed with clean water, dried, and then air-dried at 80 °C for 12 h. It was then crushed with a plant grinder and the tea powder with a particle size of 75-180 μm was collected using a standard sample sieve.

[0034] (2) Preparation of tea powder modified by in-situ polymerization of polyphenols: The solid-liquid ratio was fixed at 1:50, 5.0 g of tea powder was added to 250 mL of 0.5 mol / L hydrochloric acid solution, and then 0.5% formaldehyde by mass fraction of tea powder was added. The mixture was reacted at 70 °C for 1 h, and then filtered and washed with water until the pH of the filtrate was neutral. It was then dried at 80 °C for 12 h and set aside.

[0035] (3) Preparation of metal ion-loaded modified tea powder: The solid-liquid ratio was fixed at 1:100, and the polyphenol in-situ solidified tea powder was added to a silver ion solution with a concentration of 100 mg / L. After adsorption in a water bath for 2 h at room temperature, the mixture was filtered and the residue was collected and dried at 80 °C for 12 h for later use. The collected residue was the silver ion-loaded modified tea powder.

[0036] (4) Preparation of antibacterial tea-plastic composite materials: 30% of antibacterial modified tea powder, 59.5% of polylactic acid, 10% of glycidyl methacrylate grafted polylactic acid, and 0.5% of stearic acid were added in a color mixer according to their mass percentage and mixed evenly. The mixture was transferred to a mixer and mixed at 180 °C for 7 min at a mixing speed of 50 r / min. The mixture was then crushed into pellets using a plastic crusher. The mixed pellets were injection molded at four injection molding temperatures of 190 °C, 190 °C, 190 °C, and 90 °C, an injection pressure of 65 MPa, an injection time of 4 s, and a cooling time of 30 s.

[0037] Prepared wt %=30% silver-loaded polyphenol-cured tea residue / polylactic acid composite material, wherein the silver content of the composite material is 0.293%. The interface morphology is shown in the electron microscope. Figure 1 As shown, the tensile strength is 63.1 MPa, the flexural strength is 102.3 MPa, the notched impact strength is 22.2 J / m, and the antibacterial rate against Escherichia coli is 100% ( Figure 2 ), the antibacterial rate against Staphylococcus aureus was 100% ( Figure 3 ).

[0038] Example 3 (1) Preparation of tea powder: The tea residue was rinsed with clean water, dried, and then air-dried at 80 °C for 12 h. It was then crushed with a plant grinder and the tea powder with a particle size of 75-180 μm was collected using a standard sample sieve.

[0039] (2) Preparation of tea powder modified by in-situ polymerization of polyphenols: The solid-liquid ratio was fixed at 1:30, 5.0 g of tea powder was added to 150 mL of 0.5 mol / L hydrochloric acid solution, and then formaldehyde (0.3% by mass of the tea powder) was added. The mixture was reacted at 50 °C for 3 h, and then filtered and washed with water until the pH of the filtrate was neutral. The filtrate was then dried at 80 °C for 12 h for later use.

[0040] (3) Preparation of metal ion-loaded modified tea powder: The solid-liquid ratio was fixed at 1:100, and the polyphenol in-situ solidified tea powder was added to a silver ion solution with a concentration of 50 mg / L. After adsorption in a water bath for 3 h at room temperature, the mixture was filtered and the residue was collected and dried at 80 °C for 12 h for later use. The collected residue was the silver ion-loaded modified tea powder.

[0041] (4) Preparation of antibacterial tea-plastic composite materials: 50% antibacterial modified tea powder, 34% polylactic acid, 15% glycidyl methacrylate grafted polylactic acid, and 1% stearic acid were added into a color mixer according to their mass percentage and mixed evenly. The mixture was transferred into a mixer and mixed at 180 °C for 7 min at a mixing speed of 50 r / min. The mixture was then crushed into pellets using a plastic crusher. The mixed pellets were injection molded at four injection molding temperatures of 190 °C, 190 °C, 190 °C, and 90 °C, with an injection pressure of 80 MPa, an injection time of 4 s, and a cooling time of 30 s.

[0042] Prepared wt %=50% silver-loaded polyphenol-cured tea residue / polylactic acid composite material, in which the silver content of the composite material is 0.149%. Its tensile strength is 53.2 MPa, flexural strength is 86.7 MPa, notched impact strength is 15.9 J / m, and the antibacterial rate against Escherichia coli is 100%, and the antibacterial rate against Staphylococcus aureus is 100%.

[0043] Example 4 (1) Preparation of tea powder: The tea residue was rinsed with clean water, dried, and then air-dried at 80 °C for 12 h. It was then crushed with a plant grinder and the tea powder with a particle size of 75-180 μm was collected using a standard sample sieve.

[0044] (2) Preparation of tea powder modified by in-situ polymerization of polyphenols: The solid-liquid ratio was fixed at 1:40, 5.0 g of tea powder was added to 200 mL of 0.5 mol / L hydrochloric acid solution, and then formaldehyde was added at a mass fraction of 0.4% of the tea powder. The mixture was reacted at 60 °C for 2 h, then filtered and washed with water until the pH of the filtrate was neutral, and then dried at 80 °C for 12 h for later use.

[0045] (3) Preparation of metal ion-loaded modified tea powder: The solid-liquid ratio was fixed at 1:100, and the above-mentioned polyphenol in-situ solidified tea powder was added to a copper ion solution with a concentration of 1000 mg / L. After adsorption in a water bath for 2 h at room temperature, the mixture was filtered, and the residue was collected and dried at 80 °C for 12 h for later use. The collected residue was the copper ion-loaded tea powder.

[0046] (4) Preparation of antibacterial tea-plastic composite materials: 30% of antibacterial modified tea powder, 59% of polylactic acid, 10% of glycidyl methacrylate grafted polylactic acid, and 1% of polyethylene wax were added into a color mixer according to their mass percentage and mixed evenly. The mixture was transferred into a mixer and mixed at 180 °C for 7 min at a mixing speed of 50 r / min. The mixture was then crushed into pellets using a plastic crusher. The mixed pellets were injection molded at four injection molding temperatures of 190 °C, 190 °C, 190 °C, and 90 °C, an injection pressure of 65 MPa, an injection time of 4 s, and a cooling time of 30 s.

[0047] Prepared wt %=30% copper-loaded polyphenol-cured tea residue / polylactic acid composite material, in which the copper content of the composite material is 0.998%. Its tensile strength is 62.4 MPa, flexural strength is 103.6 MPa, notched impact strength is 22.5 J / m, and the antibacterial rate against Escherichia coli is 99.4%, and the antibacterial rate against Staphylococcus aureus is 99.7%.

[0048] Example 5 (1) Preparation of tea powder: The tea residue was rinsed with clean water, dried, and then air-dried at 80 °C for 12 h. It was then crushed with a plant grinder and the tea powder with a particle size of 75-180 μm was collected using a standard sample sieve.

[0049] (2) Preparation of tea powder modified by in-situ polymerization of polyphenols: The solid-liquid ratio was fixed at 1:20, 5.0 g of tea powder was added to 100 mL of 0.5 mol / L hydrochloric acid solution, and then formaldehyde (0.6% by mass of the tea powder) was added. The mixture was reacted at 60 °C for 3 h, and then filtered and washed with water until the pH of the filtrate was neutral. The filtrate was then dried at 80 °C for 12 h for later use.

[0050] (3) Preparation of metal ion-modified tea powder: The solid-liquid ratio was fixed at 1:100, and the above-mentioned polyphenol in-situ solidified tea powder was added to a zinc ion solution with a concentration of 500 mg / L. After adsorption in a water bath for 2 h at room temperature, the mixture was filtered and the residue was collected and dried at 80 °C for 12 h for later use. The collected residue was the antibacterial modified material of zinc ion-modified tea powder.

[0051] (4) Preparation of antibacterial tea-plastic composite materials: 30% antibacterial modified tea powder, 59% polylactic acid, 10% polylactic acid grafted with glycidyl methacrylate, 0.5% stearic acid, and 0.5% polyethylene wax were mixed in a color mixer according to mass percentage, and the mixture was transferred to a mixer and mixed at 180°C for 7 minutes at a mixing speed of 50 r / min, and then crushed into pellets using a plastic crusher. Material molding: The mixed pellets were injection molded, and the four-stage injection molding temperatures were 190°C, 190°C, 190°C, and 90°C, the injection pressure was 65 MPa, the injection time was 4 s, and the cooling time was 30 s.

[0052] Prepared wt %=30% zinc-loaded polyphenol-cured tea residue / polylactic acid composite material, in which the zinc content of the composite material is 0.816%. Its tensile strength is 62.8 MPa, flexural strength is 101.6 MPa, notched impact strength is 22.8 J / m, and the antibacterial rate against Escherichia coli is 99.8%, and the antibacterial rate against Staphylococcus aureus is 99.9%.

[0053] Example 6 (1) Preparation of tea powder: Rinse the tea residue with clean water, dry it in the air, and then dry it at 80°C for 12 h. Then, grind it with a plant grinder and collect the tea powder with a particle size of 75-180 μm using a standard sample sieve.

[0054] (2) Preparation of tea powder modified by in-situ polymerization of polyphenols: The solid-liquid ratio was fixed at 1:20, 5.0 g of tea powder was added to 100 mL of 0.2 mol / L hydrochloric acid solution, and then 0.5% formaldehyde by mass fraction of tea powder was added. The mixture was reacted at 60 °C for 1 h, and then filtered and washed with water until the pH of the filtrate was neutral. It was then dried at 80 °C for 12 h and set aside.

[0055] (3) Preparation of metal ion-modified tea powder: The solid-liquid ratio was fixed at 1:100, and the polyphenol in-situ solidified tea powder was added to a silver ion solution with a concentration of 500 mg / L. After adsorption in a water bath for 2 h at room temperature, the mixture was filtered and the residue was collected and dried at 80 °C for 12 h for later use. The collected residue was the silver-modified ion tea powder.

[0056] (4) Preparation of antibacterial tea-plastic composite materials: 30% antibacterial modified tea powder, 58% polypropylene, 10% glycidyl methacrylate grafted polypropylene, and 2% polyethylene wax were mixed in a color mixer according to mass percentage. The mixed material was transferred to a mixer and mixed at 180 °C for 7 min at a mixing speed of 50 r / min, and then crushed into pellets using a plastic crusher. The mixed pellets were injection molded at four injection molding temperatures of 190 °C, 190 °C, 190 °C, and 90 °C, with an injection molding pressure of 65 MPa, an injection molding time of 4 s, and a cooling time of 30 s.

[0057] Prepared wt %=30% silver-loaded polyphenol-cured tea residue / polypropylene composite material, in which the silver content of the composite material is 0.558%. Its tensile strength is 29.5 MPa, flexural strength is 55.3 MPa, notched impact strength is 34.3 J / m, and the antibacterial rate against Escherichia coli is 100%, and the antibacterial rate against Staphylococcus aureus is 100%.

[0058] Example 7 (1) Preparation of tea powder: The tea residue was rinsed with clean water, dried, and then air-dried at 80 °C for 12 h. It was then crushed with a plant grinder and the tea powder with a particle size of 75-180 μm was collected using a standard sample sieve.

[0059] (2) Preparation of tea powder modified by in-situ polymerization of polyphenols: The solid-liquid ratio was fixed at 1:40, 5.0 g of tea powder was added to 200 mL of 0.3 mol / L hydrochloric acid solution, and then 0.5% formaldehyde by mass fraction of tea powder was added. The mixture was reacted at 60 °C for 3 h, then filtered and washed with water until the pH of the filtrate was neutral, and then dried at 80 °C for 12 h for later use.

[0060] (3) Preparation of metal ion-loaded modified tea powder: The solid-liquid ratio was fixed at 1:100, and the above-mentioned polyphenol in-situ solidified tea powder was added to a copper ion solution with a concentration of 1000 mg / L. After adsorption in a water bath for 2 h at room temperature, the mixture was filtered and the residue was collected and dried at 80 °C for 12 h for later use. The collected residue was the copper ion-loaded modified tea powder.

[0061] (4) Preparation of antibacterial tea-plastic composite materials: 30% of antibacterial modified tea powder, 58% of polypropylene, 10% of glycidyl methacrylate grafted polypropylene, and 2% of zinc stearate were added into a color mixer according to their mass percentage and mixed evenly. The mixture was transferred into a mixer and mixed at 180 °C for 7 min at a mixing speed of 50 r / min. The mixture was then crushed into pellets using a plastic crusher. The mixed pellets were injection molded at four injection molding temperatures of 190 °C, 190 °C, 190 °C, and 90 °C, an injection pressure of 65 MPa, an injection time of 4 s, and a cooling time of 30 s.

[0062] Prepared wt %=30% copper-loaded polyphenol-cured tea residue / polypropylene composite material, wherein the copper content of the composite material is 0.999%. Its tensile strength is 29.8 MPa, flexural strength is 54.8 MPa, notched impact strength is 34.9 J / m, and the antibacterial rate against Escherichia coli is 100%, and the antibacterial rate against Staphylococcus aureus is 100%.

[0063] Example 8 (1) Preparation of tea powder: The tea residue was rinsed with clean water, dried, and then air-dried at 80 °C for 12 h. It was then crushed with a plant grinder and the tea powder with a particle size of 75-180 μm was collected using a standard sample sieve.

[0064] (2) Preparation of tea powder modified by in-situ polymerization of polyphenols: The solid-liquid ratio was fixed at 1:20, 5.0 g of tea powder was added to 100 mL of 0.6 mol / L hydrochloric acid solution, and then formaldehyde was added at a mass fraction of 0.7% of the tea powder. The mixture was reacted at 70 °C for 2 h, and then filtered and washed with water until the pH of the filtrate was neutral. The filtrate was then dried at 80 °C for 12 h for later use.

[0065] (3) Preparation of metal ion-loaded modified tea powder: The solid-liquid ratio was fixed at 1:100, and the polyphenol in-situ solidified tea powder was added to a zinc ion solution with a concentration of 1000 mg / L. After adsorption in a water bath for 2 h at room temperature, the mixture was filtered and dried. The residue collected was the zinc ion-loaded modified tea powder.

[0066] (4) Preparation of antibacterial tea-plastic composite materials: 30% of antibacterial modified tea powder, 59% of polypropylene, 10% of glycidyl methacrylate grafted polypropylene, 0.5% of bis-stearic acid amide, and 0.5% of polyethylene wax were added in a color mixer according to their mass percentage and mixed evenly. The mixture was transferred to a mixer and mixed at 180 °C for 7 min at a mixing speed of 50 r / min. 2% of calcium stearate was also added and mixed evenly. The mixed pellets were injection molded. The four-stage injection molding temperatures were 190 °C, 190 °C, 190 °C, and 90 °C, the injection pressure was 65 MPa, the injection time was 4 s, and the cooling time was 30 s.

[0067] Prepared wt %=30% zinc-loaded polyphenol-cured tea residue / polypropylene composite material, in which the zinc content of the composite material is 0.924%. Its tensile strength is 28.9 MPa, flexural strength is 56.2 MPa, notched impact strength is 33.9 J / m, and the antibacterial rate against Escherichia coli is 100%, and the antibacterial rate against Staphylococcus aureus is 100%.

[0068] Example 9 (1) Preparation of tea powder: The tea residue was rinsed with clean water, dried, and then air-dried at 80 °C for 12 h. It was then crushed with a plant grinder and the tea powder with a particle size of 75-180 μm was collected using a standard sample sieve.

[0069] (2) Preparation of tea powder modified by in-situ polymerization of polyphenols: The solid-liquid ratio was fixed at 1:20, 5.0 g of tea powder was added to 100 mL of 0.4 mol / L hydrochloric acid solution, and then formaldehyde (0.9% by mass of the tea powder) was added. The mixture was reacted at 60 °C for 2 h, and then filtered and washed with water until the pH of the filtrate was neutral. The filtrate was then dried at 80 °C for 12 h for later use.

[0070] (3) Preparation of metal ion-loaded modified tea powder: The solid-liquid ratio was fixed at 1:100, and the polyphenol in-situ solidified tea powder was added to a silver ion solution with a concentration of 400 mg / L. After adsorption in a water bath for 2 h at room temperature, the mixture was filtered and the residue was collected and dried at 80 °C for 12 h for later use. The collected residue was the silver ion-loaded modified tea powder.

[0071] (4) Preparation of antibacterial tea-plastic composite materials: 10% antibacterial modified tea powder, 78% high-density polyethylene, 10% glycidyl methacrylate grafted polyethylene, and 2% zinc stearate were added in a color mixer according to their mass percentage and mixed evenly. The mixture was transferred to a mixer and mixed at 180 °C for 7 min at a mixing speed of 50 r / min. The mixture was then crushed into pellets using a plastic crusher. The mixed pellets were injection molded at four injection molding temperatures of 185 °C, 185 °C, 185 °C, and 90 °C, an injection pressure of 60 MPa, an injection time of 4 s, and a cooling time of 30 s.

[0072] Prepared wt %=10% silver-loaded polyphenol-cured tea residue / high-density polyethylene composite material, in which the silver content of the composite material is 0.171%. Its tensile strength is 24.6 MPa, flexural strength is 37.9 MPa, notched impact strength is 37.8 J / m, and the antibacterial rate against Escherichia coli is 100%, and the antibacterial rate against Staphylococcus aureus is 100%.

[0073] Example 10 (1) Preparation of tea powder: The tea residue was rinsed with clean water, dried, and then air-dried at 80 °C for 12 h. It was then crushed with a plant grinder and the tea powder with a particle size of 75-180 μm was collected using a standard sample sieve.

[0074] (2) Preparation of tea powder modified by in-situ polymerization of polyphenols: The solid-liquid ratio was fixed at 1:20, 5.0 g of tea powder was added to 100 mL of 0.5 mol / L hydrochloric acid solution, and then formaldehyde was added at a mass fraction of 0.6% of the tea powder. The mixture was reacted at 60 °C for 2 h, then filtered and washed with water until the pH of the filtrate was neutral, and then dried at 80 °C for 12 h for later use.

[0075] (3) Preparation of metal ion-loaded modified tea powder: The solid-liquid ratio was fixed at 1:100, and the polyphenol in-situ solidified tea powder was added to a silver ion solution with a concentration of 200 mg / L. After adsorption in a water bath for 2 h at room temperature, the mixture was filtered and the residue was collected and dried at 80 °C for 12 h for later use. The collected residue was the silver ion-loaded modified tea powder.

[0076] (4) Preparation of antibacterial tea-plastic composite materials: 30% of antibacterial modified tea powder, 58% of polybutylene succinate, 10% of glycidyl methacrylate grafted polybutylene succinate, and 2% of polyethylene wax were added into a color mixer according to their mass percentage and mixed evenly. The mixture was transferred into a mixer and mixed at 145 °C for 7 min at a mixing speed of 50 r / min. The mixture was then crushed into pellets using a plastic crusher. The mixed pellets were injection molded at four injection molding temperatures of 150 °C, 155 °C, 155 °C, and 105 °C, with an injection pressure of 72 MPa, an injection time of 4 s, and a cooling time of 30 s.

[0077] Prepared wt %=30% silver-loaded polyphenol-cured tea residue / polybutylene succinate composite material, in which the silver content of the composite material is 0.393%. Its tensile strength is 20.8 MPa, flexural strength is 38.5 MPa, notched impact strength is 33.6 J / m, and the antibacterial rate against Escherichia coli is 100%, and the antibacterial rate against Staphylococcus aureus is 100%.

[0078] Comparative Example 1 The difference from Example 2 is that in step (2), "deionized water" is used instead of "hydrochloric acid solution and formaldehyde solution", and the difference from Example 2 is that in step (3), "deionized water" is used instead of "silver ion solution". wt %=30% of the original tea residue / polylactic acid composite material, the tensile strength of the composite material is 60.1 MPa, the flexural strength is 97.8 MPa, the notched impact strength is 20.7 J / m, the antibacterial rate against Escherichia coli is 33.4%, and the antibacterial rate against Staphylococcus aureus is 22.8%.

[0079] Comparative Example 2 The difference from Example 2 is that in step (3), "deionized water" is used instead of "silver ion solution". wt %=30% polyphenol in-situ cured tea residue / polylactic acid composite material, the tensile strength of the composite material is 61.7 MPa, the flexural strength is 99..8 MPa, the notched impact strength is 20.2 J / m, the antibacterial rate against Escherichia coli is 88.2%, and the antibacterial rate against Staphylococcus aureus is 65.4%.

[0080] Comparative Example 3 The difference from Example 2 is that in step (2), "deionized water" is used instead of "hydrochloric acid solution and formaldehyde solution". wt%=30% silver-loaded raw tea residue / polylactic acid composite material, the tensile strength of the composite material is 61.1 MPa, the flexural strength is 105.2 MPa, the notched impact strength is 21.8 J / m, the antibacterial rate against Escherichia coli is 96.8%, and the antibacterial rate against Staphylococcus aureus is 92.2%.

[0081] Comparative Example 4 The difference from Example 2 is that after the material is prepared, its mechanical properties and antibacterial properties are tested after being placed for one year. wt After one year of storage, the composite material of tea residue / polylactic acid in-situ cured with silver polyphenol containing 30% silver has a tensile strength of 59.4 MPa, a flexural strength of 96.2 MPa, a notched impact strength of 20.3 J / m, and an antibacterial rate of 100% against Escherichia coli ( Figure 4 ), the antibacterial rate against Staphylococcus aureus was 99.4% ( Figure 5 ).

[0082] The in-situ curing and metal loading of polyphenols in tea residues have almost no effect on the mechanical properties of the prepared tea-plastic composite material, maintaining the good mechanical properties of the composite material, but have a greater impact on the antibacterial properties of the composite material. The presence of polyphenol components in tea residues gives the tea-plastic composite material certain antibacterial properties, but the polyphenol components are easily lost during the cleaning and reaction of the tea residues; the in-situ curing of polyphenols significantly improves the antibacterial properties of the tea-plastic composite material, and its antibacterial rate against Escherichia coli is increased from 33.4% to 88.2%, and the antibacterial rate against Staphylococcus aureus is increased from 22.8% to 65.4%; after loading antibacterial metal ions, the antibacterial properties of the prepared tea-plastic composite material are further improved, and the prepared metal-loaded polyphenol-cured tea residue / resin composite material meets the Class I antibacterial effect, and its antibacterial rates against Escherichia coli and Staphylococcus aureus are both above 99%. The metal-loaded polyphenol-cured tea residues provided by the present invention can be compounded with various resins to obtain antibacterial tea-plastic materials.

[0083] The above specific embodiments are further explanations of the technical solutions and beneficial effects of the present invention, and are not limitations on the implementation methods. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.

Claims

1. An antibacterial tea-plastic composite material, characterized in that: Calculated by weight percentage as 100%, the content of each component is: antibacterial modified tea powder 10-50%, bulking agent 5-20%, resin 30-85%, and lubricant 0.5-2%.

2. The method for preparing the antibacterial tea-plastic composite material according to claim 1, characterized in that: The following steps are involved: (1) Preparation of tea powder: Wash the tea residues, air dry, grind them, and then sieve them to obtain tea powder; (2) Preparation of tea powder modified by in-situ polymerization of polyphenols: Add tea powder to hydrochloric acid solution, then add formaldehyde to react for a certain period of time, filter, and wash with water until the filtrate is neutral; (3) Preparation of antibacterial modified tea powder: adding the above-mentioned polyphenol in-situ solidified tea powder to an aqueous solution of inorganic antibacterial metal ions to react to obtain a composite antibacterial tea powder loaded with inorganic metal ions / plant polyphenols, namely, the antibacterial modified tea powder; (4) Preparation of antibacterial tea-plastic composite materials: Antibacterial modified tea powder, bulking agent, resin and lubricant are put into a color mixer and mixed evenly. The mixture is then transferred to a mixer. After mixing evenly, the material is discharged and crushed into pellets using a plastic crusher. The antibacterial tea-plastic composite material is obtained by injection molding.

3. The method for preparing the antibacterial tea-plastic composite material according to claim 2, characterized in that: The tea residue in step (1) is sourced from any one or more of tea tree branches, tea stems, tea powder, tea leaves, and tea processing waste, and has a particle size of 75-180 μm.

4. The method for preparing the antibacterial tea-plastic composite material according to claim 2, characterized in that: The material-liquid ratio of tea powder to hydrochloric acid solution in step (2) is 1:10-1:50, the concentration of hydrochloric acid solution is 0.2-0.6 mol / L, the mass fraction of formaldehyde added is 0.1-0.9% of the mass of tea powder, the reaction temperature is 50-80°C, and the reaction time is 1-3 h.

5. The method for preparing the antibacterial tea-plastic composite material according to claim 2, characterized in that: The inorganic antibacterial ions in step (3) are one or more of silver ions, zinc ions and copper ions, the sources of the inorganic antibacterial ions are the corresponding silver nitrate, zinc nitrate and copper nitrate, the concentration of the inorganic antibacterial ions is 50-1000 mg / L, the solid-liquid ratio of the polyphenol in-situ solidified tea powder and the aqueous solution of the inorganic antibacterial metal ions is 1:20-1:200, the reaction temperature is room temperature, and the reaction time is 0.5-4h.

6. The method for preparing the antibacterial tea-plastic composite material according to claim 2, characterized in that: In the step (4), the resin is one or more of polylactic acid, polypropylene, and high-density polyethylene; the compatibilizer is glycidyl methacrylate grafted resin; and the lubricant is at least one of stearic acid, polyethylene wax, zinc stearate, calcium stearate, and bis-stearic acid amide.

7. The method for preparing the antibacterial tea-plastic composite material according to claim 2, characterized in that: The mixing temperature in step (4) is 140-180°C, the mixing time is 5-8 min, and the mixing speed is 40-60 r / min.

8. The method for preparing the antibacterial tea-plastic composite material according to claim 2, characterized in that: The four-stage temperatures of the injection molding in the step (4) are 150-190°C, 150-190°C, 150-190°C, and 80-120°C, the injection pressure is 50-100 MPa, the injection time is 3-5 s, and the cooling time is 15-45 s.